Empowering Future Leaders through Literacy: A Comprehensive Workshop for Elementary School Educators - Alief Noor Farida; Zulfa Sakhiyya; Pasca Kalisa; Girindra Putri Dewi Saraswati; Issy Yuliasri (Jurnal Abdimas, 2024)
Building students’ literacy skills needs to be done as early as possible. Elementary school students are at the perfect age of getting much exposure to literacy. Therefore, teachers need to be able to do some activities in the classrooms that build literacy skills. However, not all teachers know and apply the teaching techniques proposed by the Ministry of Education and Culture in school literacy movement. This community service aimed to address the needs of elementary school teachers, members of Bawana Alit group, in Tembalang, Semarang, on literacy teaching techniques. The goal was to empower these members with practical skills in implementing literacy teaching techniques in their classroom, depending on their students’ literacy levels. This workshop involved some stages, including preparation and implementation. The participants now have more effective literacy teaching strategies to be applied in their classrooms.